2015
DOI: 10.1111/jhn.12332
|View full text |Cite
|
Sign up to set email alerts
|

A nested case–control study on dietary fat consumption and the risk for gallstone disease

Abstract: According to our results, total fat, saturated and monounsaturated fatty acids high intakes are associated with increased GD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
3
11
0
1
Order By: Relevance
“…There has been no study that differentiated cholesterol and pigment gallstones in relation to diet. Previous studies reported that the risk of gallstone was positively associated with intake of meat [ 6 ], fat, and saturated fat in Europeans [ 7 , 8 , 13 , 19 ]. Meat, a major source of fat and saturated fat, was positively associated with risk of gallstones, while unsaturated fatty acid was negatively associated [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been no study that differentiated cholesterol and pigment gallstones in relation to diet. Previous studies reported that the risk of gallstone was positively associated with intake of meat [ 6 ], fat, and saturated fat in Europeans [ 7 , 8 , 13 , 19 ]. Meat, a major source of fat and saturated fat, was positively associated with risk of gallstones, while unsaturated fatty acid was negatively associated [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSD is multifactorial in origin, including genetic and dietary factors [5]. Many risk factors are associated, such as weight, age, dyslipidemia, chronic liver disease, gender, and parity [6].…”
Section: Introductionmentioning
confidence: 99%
“…El consumo de comida chatarra en nuestra investigación resultó con significación estadística; se evidenció que los pacientes que no tenían cálculos en la vesícula tenían un consumo de comida chatarra menor de 2 días a la semana; a diferencia de los que sí tenían colelitiasis (diagnosticados por ecografía abdominal) donde consumían por lo menos 2 veces a la semana comida chatarra; esto se apoya con lo encontrado por los estudios de Compagnucci y Park quienes demostraron que el consumo de grasas saturadas y monoinsaturadas incrementaban el riesgo de cálculos en la vesícula 7,15 , adicionalmente a esto, Lander encontró que el consumo de proteínas vegetales disminuía el riesgo de padecer cálculos de la vesícula 16 . En Chile, del Pozo, en un estudio experimental en ratones concluye que la ingestión de una dieta alta en grasas, y en mayor predominio grasas saturadas, podría contribuir a la formación de cálculos de colesterol en la VB, principalmente, en un estadio temprano 17 .…”
Section: Discussionunclassified